2023
DOI: 10.1111/ppe.13002
|View full text |Cite
|
Sign up to set email alerts
|

Small for gestational age preterm infants and later adiposity and height: A systematic review and meta‐analysis

Abstract: BackgroundOverweight and obesity and their consequent morbidities are important worldwide health problems. Some research suggests excess adiposity origins may begin in fetal life, but unknown is whether this applies to infants born preterm.ObjectiveThe objective of the study was to assess the association between small for gestational age (SGA) birth and later adiposity and height among those born preterm.Data sourcesMEDLINE, EMBASE and CINAHL until October 2022.Study selection and data extractionStudies were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…In our study, BMI was observed to be lower among SGA individuals in both remote and urban regions with the difference in urban regions being far more pronounced. This is consistent with other studies reporting that those born SGA have a lower BMI later in life ( 26 , 37 ). Two Australian studies analysing data from a remote Indigenous community in the Northern Territory found BMI to be inversely associated with all-cause mortality after follow-up at 9 years ( 38 ) and 18 years ( 39 ), however, increased WC was associated with increased risk of all-cause mortality ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, BMI was observed to be lower among SGA individuals in both remote and urban regions with the difference in urban regions being far more pronounced. This is consistent with other studies reporting that those born SGA have a lower BMI later in life ( 26 , 37 ). Two Australian studies analysing data from a remote Indigenous community in the Northern Territory found BMI to be inversely associated with all-cause mortality after follow-up at 9 years ( 38 ) and 18 years ( 39 ), however, increased WC was associated with increased risk of all-cause mortality ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results consistently demonstrate lower anthropometric measurements in the SGA individuals from childhood through young adult, indicating that through their life course those born SGA are smaller than those born non-SGA. Although current literature on SGA and body composition later in life among Indigenous Australians is limited, our findings align with other studies (from Sweden, Netherlands, Japan, Greece, and a meta-analysis) reporting that individuals born SGA tend to be smaller during childhood (23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 90%
“…Preterm birth, small-for-gestational-age (SGA) birth, and low birth weight (LBW) are major adverse birth outcomes that are risk factors for neonatal and infant mortality [ 1 3 ], and these birth outcomes can also affect children’s neurodevelopmental outcomes and body mass index (BMI) [ 4 , 5 ]. It is known that the LBW rate among singleton births has been decreasing in recent years in Japan (from 8.39% in 2010 to 8.14% in 2019) [ 6 ], while the rate of preterm birth has remained relatively constant (approximately 5.6%) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, there are some studies that investigated trends in birth outcomes, and one study showed that the number of total births significantly decreased in Japan after the pandemic [ 16 ]. In addition, there are some studies that investigated trends in adverse birth outcomes and fetal mortality over the decades in Japan using national data [ 5 , 6 , 17 ], while such studies did not evaluate the effect of the pandemic. Moreover, there are some studies that investigated an effect of the pandemic on adverse birth outcomes or threatened preterm labor in Japan [ 18 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several myths surround the growth of preterm and small infants, which are often founded in the prevalent misconceptions that fetal and infant growth patterns solely and strongly predict future risks of obesity, cardiovascular disease, and metabolic disorders [ 9 ]. Preterm and small infants are not necessarily at higher risk of obesity and cardiovascular disease in the long term [ [10] , [11] , [12] , [13] ] (see below under Growth of SGA infants). The long-term risks for obesity and cardiovascular disease are influenced by a combination of modifiable and nonmodifiable factors, including genetics, social determinants of health, prenatal history, and nutrition [ [14] , [15] , [16] , [17] , [18] , [19] ] ( Figure 1 [ [20] , [21] , [22] , [23] , [24] , [25] ]), as well as later life lifestyle choices (including physical activity, nutrition, and energy balance).…”
Section: Introductionmentioning
confidence: 99%